2018
DOI: 10.1016/j.apenergy.2018.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Multi-time scale coordination of complementary resources for the provision of ancillary services

Abstract: This paper presents a predictive control scheme for coordinating a set of heterogeneous and complementary resources at different time scales for the provision of ancillary services. In particular, we combine building thermodynamics (slow), and energy storage systems (fast resources) to augment the flexibility that can be provided to the grid compared to the flexibility that any of these resources can provide individually. A multi-level control scheme based on data-based robust optimization methods is developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the so called demand response (DR) scenario, power consumption is adjusted -not necessarily reduced -in real-time with the objective of contributing to the grid power balance [Yoon et al, 2014]. Due to their significant energy consumption in conjunction with their inherent large inertia, it has been shown that buildings are suitable candidates for this task [Fabietti et al, 2018b, Luc et al, 2018, Pallonetto et al, 2019. DR programs are furthermore expected to grow significantly in the next years (see e.g.…”
Section: Three-way Valvementioning
confidence: 99%
See 1 more Smart Citation
“…In the so called demand response (DR) scenario, power consumption is adjusted -not necessarily reduced -in real-time with the objective of contributing to the grid power balance [Yoon et al, 2014]. Due to their significant energy consumption in conjunction with their inherent large inertia, it has been shown that buildings are suitable candidates for this task [Fabietti et al, 2018b, Luc et al, 2018, Pallonetto et al, 2019. DR programs are furthermore expected to grow significantly in the next years (see e.g.…”
Section: Three-way Valvementioning
confidence: 99%
“…This in turn triggers time-dependent or demand-dependent electricity tariffs and a general rise of energy prices. We believe that the most systematic method to deal with these factors while minimizing operating is MPC rather than the previous alternatives (see [Fabietti et al, 2018b] for an example of a realistic DR thermal control study).…”
Section: How Far Are We From the Ideal Solution?mentioning
confidence: 99%
“…[23] incorporates wind power based on energy storage and proposes a real-time cooperative scheme for the joint participation of wind storage in the energy and ancillary services markets, taking advantage of their complementary nature and significantly increasing the overall revenue. The literature [24] proposes a predictive control scheme for coordinating the provision of ancillary services from heterogeneous complementary resources at different time scales. Additionally, the literature [25], thinking from the user side, proposes a two-way smart charging algorithm for electric vehicles considering user preferences, peer-to-peer power trading, and the provision of ancillary services to the grid.…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of demand resources, heating, ventilation and air-conditioning (HVAC) systems in buildings are one of the most promising sources to provide frequency regulation service [8]. The reasons are that they account for a large proportion of electric energy consumption [9,10], and because of thermal inertia of buildings and HVAC systems, they have great power use flexibility [11].…”
Section: Introductionmentioning
confidence: 99%